Employee Performance Improvement at PT Cahaya Abadi Terang Medan Is Based on the Work Environment, Work Motivation, and Work Discipline - M. Sofyan Hasan Lubis; Yohny Anwar; Muhammad Isa Indrawan (SIASAT, 2022)
This research discusses the partial or simultaneous effect of environment factors, motivation, and discipline on employee performance at PT Cahaya Abadi Terang. A questionnaire was used to gather data from 65 employees of PT Cahaya Abadi Terang. This paper uses multiple linear regression. The study findings demonstrate a substantial simultaneous effect between the three factors and a partly significant influence between environment, motivation, and disciplinary variables on employee performance.